Sequencing to identify pathogens in Tenebrio molitor: Implications in insects farmed for food and feed - Leierer, Dewey; Olmstead, Morgan; Oppert, Brenda (Frontiers in Insect Science, 2023)
The farmed insect industry is increasing in number and size to meet the demand for sustainably-produced protein. Larger insect farms are prone to losses due to pathogens, and more information is needed regarding the health of insects reared for food and feed. In this study, high throughput sequencing was used to identify potential pathogens in a colony of Tenebrio molitor (yellow mealworm, Coleoptera: Tenebrionidae) that exhibited increased mortality in immature stages with eventual colony collapse. Sequences also were obtained from a healthy new colony of T. molitor, as well as a recovered individual from the collapsed colony. Screening of sequences obtained from the colonies and their rearing diet indicated that the collapsed colony had low diversity in microbial taxa, with predominantly sequences from the families Staphylococcaeceae and Streptococcaceae constituting from 53 to 88% of the total microbial reads. Conversely, in the new colony and their rearing diet, microbial sequences were from more than 15 different taxa, with Lactobacilleceae the most prevalent but representing only 21% of the total microbial reads. Evidence indicates that Bacillus thuringiensis may have been involved in the collapse of the colony, leading to sepsis and microbial dysbiosis, although the source of the bacteria was not identified. Sequences from the recovered individual reflected a microbial flora profile that was intermediate between those of the diseased collapsed and new colonies. These findings have implications for insects reared in confined environments and provide a rapid method to screen insect colonies by sequencing healthy and potentially diseased individuals.